The behaviour of young workers towards retirement planning in Kota Bharu, Kelantan / Nurizkiyyah Ramli - Ramli, Nurizkiyyah (Faculty of Business and Management, 2018)
Retirement planning refers to a strategic approach that must consider very well by every working people. Retirement planning can help an individual to enjoy the quality of life during retires which gives a lot of advantages so that they no need to worry about their available resources in the future. However, the young workers, they feel that the retirement still far away and makes them do not worry about their retirement planning for their future benefits. Hence, in order to survive during retirement, some of retire has insufficient saving for support their life was spent the savings in between three and five years only after retirement. For the past few years, most young workers in Malaysia not concern about the financial areas especially about the implications of saving in their lives. The results identified that materialism not significant with the retirement planning behaviour. It can see among the young workers wants to be look as rich people in front other people. Besides, they think that they need to use all money from what have earned for current spending patterns and with plans to live comfortably until they forget that they still need to save some for their retirement. Workers want to live comfortably during retirement but most of them still not concern about retirement planning. This scene may rise due to some factors that affect the behaviour of young workers towards retirement, which will be done at Kota Bharu, Kelantan.